PLANTING CHARACTER EDUCATION VALUES THROUGH THE MORAL EDUCATION PERSPECTIVE OF SYEH JA'FAR AL-BARZANJI - Nurhidayati, Titin; Kurniasih, Apri; Rofiq, M. Nafiur (LPPM STAI DARUSSALAM LAMPUNG, 2024)
This article aims to examine the literary works of Muslim writers who have played an important role throughout history in the spread of Islam to remember that literary works are not limited to da'wah in the narrow sense, but also as teachings and foundations for Muslim culture. Through Syekh Ja'far Al-Barzanji's literary works, the ethical, moral, and Islamic values ​​of life are indigenized on a socio-cultural fundamentalist basis in society. The Al-Barzanji book contains the majesty of the Prophet as a role model for mankind. Likewise, the noble values ​​of the personality of the Prophet make reflections for the readers in each of his verses. The values ​​of character education through moral education in Syair Al-Barzanji include how: 1) selecting teachers and the environment for students, 2) honesty in requests, 3) finding a life partner. Meanwhile, the moral values ​​described in Al-Barzanji's poetry include how: 1) morals in association, 2) morals towards children, 3) morals to Allah SWT, 4) morals to parents, 5) morals to the profession, 6) morals to always consult, 7) morals towards people who have wronged them, 8) morals towards families, 9) morals towards weak people and leaders, 10) morals in anger, and 11) morals in Simplicity.